Uremic Pruritus In End-Stage Renal Disease Patients Receiving Three Times Weekly Hemodialysis a Multi-Center Study - Mazhar Ul Haq, Rahmat Ali Khan, Syed Munib, Muhammad Shahid, Shah Fahad, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To quantify the prevalence of uremic pruritus in ESRD patients receiving maintenance hemodialysis three times per week. Study Design: Analytical cross-sectional research Place and Duration of Study: Institute of kidney diseases Peshawar from May 1, 2021, to April 25, 2022. Methodology: A total of 32 adult patients receiving hemodialysis for a period more significant than three months were included in the study, while those receiving hemodialysis for acute kidney injury for less than three months or displaying clinical or laboratory signs of other conditions, such as chronic skin disease, cholestasis, and malignancies, were excluded. Results: There were 9 (28.1%) females and 23 (71.9%) men, with a mean age of 45, 13.29 years. The patients' average BMI was 23.73 kg/m2. 15 (46.9%) of the participants had diabetes, whereas 17 (53.1%) did not. 27 (84.4%) were discovered to have hypertension, while 3 (9%) were normotensive, 2 (6.2%) were taking HD for six months to a year, while 9 (28.1%), 23 (71.9%), and >3 years were the appropriate HD treatment durations. Conclusion: Uremic pruritis affects 23.1% of individuals receiving thrice-weekly MHD in our study. Keywords: End-stage renal disease, uremic pruritis, and hemodialysis